ECOTOXICOLOGICAL IMPACT OF PLASTIC ON SELECTED AQUATIC AND TERRESTRIAL HABITATS OF MALETE MORO LOCAL GOVERNMENT AREA OF KWARA NORTH CENTRAL, NIGERIA - Akanbi-Gada, Mariam Abiola; Amubieya, Omolara Faith; Owoleke, Veronica Amina; Jimoh, Akeem Adebayo; Sule, Bilikisu Tope; Olabamiji, Segun Tayo; Najeemdeen, Bolaji Abiodun; Idris, Gbolahan David (FUDMA JOURNAL OF SCIENCES, 2025)
Plastic pollution is now a major environmental issue that has a significant impact on ecosystems all around the world. The aim of this research was to examine the ecotoxicological effects of plastic pollution on the aquatic water bodies and terrestrial habitats, in urban centers and waste disposal sites of Malete Community, Kwara State, Nigeria. Plastic samples were collected from three sampling points with the following coordinates, (Latitude 8° 71’ 8" and longitude 4° 46’ 8"), (Latitude 80 70’ 8" Longitude 40 46’ 8"), and (Latitude 8° 70’ 8" and longitude 4° 46’ 8") and they were tagged samples 1, 2 and 3 respectively, this was done as a representative of aquatic and terrestrial ecosystems. Gas Chromatography-Mass Spectrometry (GC-MS) analysis as well as chemical characterization of the plastic samples were carried out using standard procedures and methodologies. Interestingly, sample 1 has high levels of the following compounds, benzene (8.3%) ethylbenzene (22.6, %) and styrene (45.2%), known to have harmful impacts on aquatic life. The presence of 1-Octene (18.9%) and 1-Nonene (22.6%) in Sample 2 indicated the possibility of biomagnification through food chain. The presence of ethyl terephthalate (25.9%), and ethylene glycol (19.3%), which are compounds associated with aquatic toxicity, was evident in Sample 3. This study highlights the widespread ecotoxicological impact of plastic pollution in the aquatic and terrestrial ecosystems of Malete Community, Kwara State. The presence of hazardous compounds in the plastic samples suggests significant risks to environmental health.